Use of digital media for family planning information by women and their social networks in Kenya: A qualitative study in peri-urban Nairobi - Zinke-Allmang, Anja; Hassan, Rahma; Bhatia, Amiya; Gorur, Krittika; Shipow, Amy; Ogolla, Concilia; Shirley, Sarah; Keizer, Kees; Cislaghi, Beniamino (Frontiers in Sociology, 2022)
Access to information about family planning (FP) continues to have financial, physical and social barriers among young women living in Kenya. This paper draws on social norms theory to explore how young women and their social networks access FP information on digital media (e.g., WhatsApp, websites). Qualitative phone interviews were conducted with 40 participants -- young women, their partners and key influencers -- in seven peri-urban wards in Nairobi, Kenya. Data were analysed using thematic analysis. Findings suggested that young women, their partners and key influencers predominately accessed FP information online through their informal networks, but identified healthcare workers as the most trusted sources of FP information. In digital spaces, participants described being more comfortable sharing FP information as digital spaces allowed for greater privacy and reduced stigma to talk about FP openly. Our findings highlight the importance of digital media in disseminating FP information among young women and their networks, the differences in norms governing the acceptability to talk about FP online versus in-person and the significance of targeting misinformation about FP in digital media spaces.